Faktor Determinan Host dengan Kejadian Diare pada Balita di Indonesia : Tinjauan Literatur - Istikhomatul Ulya; Achmad Syaiful Islam; Kusuma Scorpia Lestari (Media Gizi Kesmas, 2025)
Background: Toddler diarrhea is a major Indonesian health concern. Toddler diarrhea rates differ in the 2021 SSGI data. West Sulawesi, NTB, and Maluku have the most diarrhea. This study investigates the causes of Indonesian toddler diarrhea. Objectives: This research is intended to systematically analyze host-related determinants that contribute to the occurrence of diarrhea in Indonesian toddlers from 2021 to 2025. Methods: PRISMA 2020 guided systematic reviews. Google Scholar, ScienceDirect, and PubMed provided data. Eight 2021–2025 studies examined Indonesian toddler diarrhea risk variables. Newcastle-Ottawa Scale and internal validation questions rated quality. Results: From the screening process, eight studies were determined to satisfy the inclusion criteria.  The synthesis of these studies showed that several host characteristics, including toddler’s age, practice of exclusive breastfeeding, and immunization completeness, show a meaningful association with diarrhea prevalence among young children in Indonesia. Conclusion: Age, exclusive breastfeeding, and immunization status significantly affected Indonesian toddler diarrhea incidence, although nutritional condition and gender did not.